Intermediate transfer sheet

The intermediate transfer sheet with a tailored release layer composition and peeling force range addresses burr and transferability issues, achieving robust and durable image transfer on diverse materials.

JP2024174359APending Publication Date: 2024-12-17FUJI COPIAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023092150
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Existing intermediate transfer sheets face issues with transfer layer burrs and poor transferability to various materials due to insufficient peeling force control, leading to primary transfer failures and reduced durability of images on transfer objects.

Method used

The intermediate transfer sheet is designed with a specific composition of a release layer containing polyester resin or polyester urethane resin, colloidal silica, and thermoplastic resin, with a glass transition point between -30°C and -5°C, and a peeling force of 0.03 N/18 mm to 0.20 N/18 mm, ensuring easy peeling and robust transfer without burrs.

Benefits of technology

The solution provides excellent transferability and durability of images on transfer targets, preventing burrs and ensuring reliable transfer to various materials without primary transfer failures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174359000001_ABST
    Figure 2024174359000001_ABST
Patent Text Reader

Abstract

To provide an intermediate transfer sheet that ensures smooth transfer of a transfer layer from the intermediate transfer sheet to a body to be transferred, prevents the formation of burrs on the transfer layer during transfer, and ensures excellent durability for an image on the body to be transferred.SOLUTION: A intermediate transfer sheet has a substrate, with at least a release layer, a protective layer, and an image-receiving layer sequentially laminated as transfer layers on the substrate. The release layer contains polyester resin and / or polyester urethane resin with a glass transition point of -30°C or more and -5°C or less, colloidal silica, thermoplastic resin, and wax. In a solid content of the release layer, the polyester resin and / or the polyester urethane resin, and the colloidal silica are present within specific content ranges, respectively.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an intermediate transfer sheet for an intermediate transfer system in which an image is recorded on a transfer layer of the intermediate transfer sheet by thermal melt transfer, and then the transfer layer is retransferred to a receiving material by a heated roll or hot stamp, etc., to form a printed matter. [Background technology]

[0002] Conventionally, a thermal transfer recording method using a thermal transfer sheet having a heat-melting type colored ink layer has been known as a method for forming an image on a transferee such as an ID card. In this method, energy is applied to a thermal transfer sheet having a heat-melting type colored ink layer using a thermal head, and the heat-melting type colored ink layer is thermally transferred to form characters or images on the transferee. In addition, from the viewpoint of improving the robustness of characters and images formed on a transferee such as an ID card, an intermediate transfer method is widely used in which characters or images are formed on the transfer layer of an intermediate transfer sheet having a transfer layer using a thermal transfer sheet having a heat-melting type colored ink layer (primary transfer), and then the transfer layer is transferred together with the image to the transferee by a heat roll or hot stamp (secondary transfer) to form characters or images.

[0003] Patent Document 1 discloses a thermal transfer printer that has a control unit that controls the card feed speed in a transfer section based on the material of the card, in which an intermediate transfer medium having a receptor layer on which an image is formed by a color material layer of a thermal transfer sheet and a card are heated while being fed in a superimposed state, and the transfer layer on which the image is formed is transferred onto the card, in order to improve the transferability of the transfer layer from an intermediate transfer medium (intermediate transfer sheet) to a card regardless of the material of the card (receiving body) and to prevent a decrease in production efficiency. Patent Document 1 discloses a thermal transfer printer that has a control unit that controls the card feed speed in a transfer section based on the material of the card, in which an intermediate transfer medium having a receptor layer on which an image is formed and a card are heated while being fed in a superimposed state, and the transfer layer on which the image is formed is transferred onto the card, in order to improve the transferability of the transfer layer from the intermediate transfer medium to the card regardless of the material of the card, in accordance with the card feed speed of the thermal transfer printer.

[0004] On the other hand, a method for improving the transferability of the transfer layer of the intermediate transfer sheet to cards of various materials is to reduce the peeling force between the substrate and the transfer layer of the intermediate transfer sheet. The smaller the peeling force between the substrate and the transfer layer, the better the transferability of the transfer layer to cards of various materials, and it becomes unnecessary to provide a control unit on the thermal transfer printer side to control the card feed speed according to the card material.

[0005] However, if the peeling force between the substrate and the transfer layer of the intermediate transfer sheet is reduced, when the transfer layer is transferred from the intermediate transfer sheet to the entire surface of a card, which is a transferee, using a heat roll or the like, a problem occurs in that the transfer layer peels off from the substrate in a planar manner together with the transfer layer attached to the card at the end of the card, resulting in "burrs." In addition, if the peeling force between the substrate and the transfer layer is small, the transfer layer may peel off from the substrate during primary transfer, in which characters or images are formed on the transfer layer using a thermal transfer sheet, resulting in primary transfer failure.

[0006] Patent Document 2 discloses an intermediate transfer sheet in which the peeling layer is made of acrylic resin, polyester resin, and a ketone formaldehyde resin joint agent, as an intermediate transfer sheet that maintains the transfer efficiency of the transfer layer while preventing transfer defects such as tailing or burrs. However, the peeling force is not small enough to ensure good transferability of the transfer layer to cards of various materials.

[0007] Furthermore, since characters and images formed on the surface of an ID card or the like usually require high robustness, the transfer layer of the intermediate transfer sheet has a protective layer made of a thermoplastic resin or a curable resin with good robustness, such as an acrylic resin or a polyester resin. However, a transfer layer having such a protective layer has poor film cutting properties, and when the peeling force between the substrate and the transfer layer is reduced to improve the transferability of the transfer layer to cards of various materials, it is difficult to obtain a transfer layer without burrs. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2019-104207 A [Patent Document 2] JP 2004-351639 A Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention aims to provide an intermediate transfer sheet which has good transferability of a transfer layer having an image formed thereon to a recipient when the transfer layer is transferred from the intermediate transfer sheet to the recipient over its entire surface with a heated roll, which suppresses the generation of burrs in the transfer layer during transfer, and which provides excellent robustness of the image on the recipient. [Means for solving the problem]

[0010] The intermediate transfer sheet of the present invention is an intermediate transfer sheet having a base material and at least a release layer, a protective layer, and an image receiving layer laminated thereon in that order as transfer layers, the release layer containing a polyester resin and / or a polyester urethane resin having a glass transition point of -30°C or more and -5°C or less, colloidal silica, a thermoplastic resin, and a wax, and the solid content of the release layer contains 2.0% by mass or more and 8.0% by mass or less of the polyester resin and / or polyester urethane resin, and 60.0% by mass or more and 70.0% by mass or less of the colloidal silica.

[0011] In one embodiment of the intermediate transfer sheet of the present invention, the peel strength of the transfer layer of the intermediate transfer sheet, as measured by the following measurement method, is 0.03 N / 18 mm or more and 0.20 N / 18 mm or less.

[0012] (Peel force measurement method) The intermediate transfer sheet is cut to a width of 25 mm, and an 18 mm wide adhesive tape is attached to the image receiving layer surface of the intermediate transfer sheet so that it is parallel to the length direction and does not extend beyond the width direction of the intermediate transfer sheet. A 19.6 N (2 kgf) rubber roller is rolled back and forth twice over the adhesive tape to bond it, and the sheet is left for 24 hours in an environment of 23±2°C and 50±10% RH. After that, a T-peel test is performed using a tensile testing machine at a peel speed of 3.0 m / min in an environment of 23±2°C and 50±10% RH, and the peel force at this point is measured. Effect of the Invention

[0013] According to the intermediate transfer sheet of the present invention, an image can be formed on the thermal transfer sheet without any problems, and when the transfer layer on which the image has been formed is transferred from the intermediate transfer sheet to the receiving material using a heated roll, the peel force between the substrate and the release layer is small, the transferability of the transfer layer to the receiving material is good, no burrs are generated in the transfer layer during transfer, and an intermediate transfer sheet can be provided in which the robustness of the image on the receiving material is excellent. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of the intermediate transfer sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the intermediate transfer sheet of the present invention will be described in detail.

[0016] <Intermediate transfer sheet> An embodiment of the intermediate transfer sheet of the present invention is an intermediate transfer sheet 1 having a substrate 2 on which a release layer 3, a protective layer 4, and an image receiving layer 5 are sequentially laminated, as shown in FIG. 1, and the transfer layer 6 to be transferred to the transfer recipient includes the release layer 3, the protective layer 4, and the image receiving layer 5.

[0017] (base material) As the substrate used in the intermediate transfer sheet of the present invention, various plastic films such as polyester films such as polyethylene terephthalate film and polyethylene naphthalate film, polypropylene film, polycarbonate film, polyimide film, aramid film, etc. can be used. Among these, from the viewpoint of the peelability of the transfer layer of the intermediate transfer sheet of the present invention, it is preferable to use a polyester film, and it is more preferable to use a polyethylene terephthalate film. The thickness of the substrate is usually about 5 to 30 μm, and in order to improve heat transfer, it is preferably in the range of 5 to 20 μm.

[0018] (Release layer) The release layer of the intermediate transfer sheet of the present invention has an easy peeling property that holds the transfer layer without peeling from the substrate before heating and easily peels the transfer layer from the substrate by heating, and a film tearability that suppresses the occurrence of burrs (planar peeling) in the transfer layer. Furthermore, the release layer becomes the outermost layer of the transfer layer transferred to the transfer recipient, and also functions as a surface protection layer.

[0019] In order to satisfy the above-mentioned performance requirements, the release layer of the present invention contains, as essential components, a polyester resin and / or a polyester urethane resin having a glass transition point of -30°C or higher and -5°C or lower, colloidal silica, a thermoplastic resin, and a wax.

[0020] The release layer of the present invention contains a polyester resin and / or a polyester urethane resin having a glass transition point (Tg) of -30°C or more and -5°C or less in order to provide adhesion to the substrate and flexibility to the release layer. If the glass transition point (Tg) is less than -30°C, the release layer becomes soft and the robustness decreases. On the other hand, if the glass transition point (Tg) is more than -5°C, the peeling force from the substrate increases and the transferability decreases. Therefore, it is preferable that the glass transition point (Tg) is in the above range. If it is in the above range, a release layer having appropriate adhesion and flexibility can be obtained, and the balance between the retention performance and transferability of the transfer layer can be good, and the film cutting property and robustness can be good. In this specification, the glass transition point (Tg) is a value measured at a temperature rise rate of 20°C / min using a differential scanning calorimeter in accordance with JIS K7121.

[0021] The polyester resin may be a polyester copolymer resin obtained by copolymerizing a dicarboxylic acid with a glycol compound. The polyester urethane resin may be obtained by reacting a polyester resin having two or more functional groups such as hydroxyl groups in one molecule with a polyisocyanate compound.

[0022] From the viewpoint of adhesion and film tearability, the number average molecular weight (Mn) of the polyester resin and / or polyester urethane resin is preferably 10,000 or more and 40,000 or less. In this specification, the number average molecular weight (Mn) is a number average molecular weight calculated based on standard polystyrene as measured by gel permeation chromatography (GPC).

[0023] The content of polyester resin and / or polyester urethane resin in the release layer is preferably 2.0% by mass or more and 8.0% by mass or less. If the content is less than 2.0% by mass, the release layer may peel off from the substrate before use, causing the transfer layer to fall off (so-called powder fall), or transfer may be poor during primary transfer with a thermal transfer sheet. Furthermore, sufficient film cutting properties cannot be imparted during secondary transfer, resulting in burrs. On the other hand, if the content exceeds 8.0% by mass, the peeling force with the substrate increases, and good transferability cannot be obtained.

[0024] The release layer contains colloidal silica to provide film tearability, reduce peeling force, and ensure transparency. The content of colloidal silica is preferably 60.0% by mass or more and 70.0% by mass or less. If the content is less than 60.0% by mass, sufficient film tearability cannot be provided during transfer of the transfer layer, and burrs are generated in the transfer layer. On the other hand, if the content is more than 70.0% by mass, the film strength of the release layer is insufficient, and the robustness of the transfer layer as the outermost layer is reduced.

[0025] From the viewpoint of the film cutting property and transparency of the transfer layer, the average particle diameter of colloidal silica is preferably from 10 nm to 100 nm, and more preferably from 10 nm to 50 nm. In this specification, the average particle diameter of colloidal silica is a value measured using a method of conversion from the specific surface area by the BET method, and is a value calculated by the following formula assuming that the particles are true spheres: d=6000 / (S×ρ) (d: average particle diameter (nm), S: specific surface area (m2 / g), ρ: true specific gravity (g / cm 3 ))

[0026] The release layer contains a thermoplastic resin having good releasability from the substrate in addition to the polyester resin and / or polyester urethane resin. Examples of the thermoplastic resin include acrylic resin, butyral resin, epoxy resin, ketone resin, and petroleum resin. Among these, it is preferable to use an acrylic resin in terms of releasability and robustness, and it is particularly preferable to use an acrylic resin having a glass transition point (Tg) of 100° C. or higher. The content of the thermoplastic resin in the release layer is preferably 10.0% by mass or more and 35.0% by mass or less in terms of layer strength and releasability.

[0027] The release layer contains wax to reduce the peeling force and provide slipperiness. Examples of wax include vegetable waxes such as candelilla wax and carnauba wax, animal waxes such as lanolin and whale wax, mineral waxes such as montan wax, petroleum waxes such as paraffin wax and microcrystalline wax, synthetic hydrocarbon waxes such as polyethylene wax and polypropylene wax, and oxidized waxes or partially modified waxes thereof, fatty acid esters, fatty acid amides, etc. The wax content in the release layer is preferably 1.0% by mass or more and 10.0% by mass or less from the viewpoint of peeling property and slipperiness.

[0028] The release layer may contain various additives as necessary, such as a plasticizer, a defoamer, a surfactant, an antioxidant, and a dispersant.

[0029] The thickness of the release layer is preferably 0.5 μm or more and 3.0 μm or less from the viewpoints of releasability of the transfer layer and film tearability.

[0030] The release layer can be formed by dispersing or dissolving each of the above-mentioned components in a suitable solvent to prepare a coating liquid, applying the coating liquid to a substrate by a known means such as roll coating, reverse roll coating, gravure coating, reverse gravure coating, bar coating, or rod coating to form a coating film, and then drying the solvent.

[0031] (protective layer) In the intermediate transfer sheet of the present invention, a protective layer is provided on the release layer formed on the substrate. The protective layer is a layer for imparting abrasion resistance, chemical resistance, etc. to the image secondarily transferred to the transfer-receiving material, and improving the robustness and durability of the image.

[0032] The protective layer contains a resin material as a main component, and examples of the resin material include polyester resin, acrylic resin, epoxy resin, styrene resin, polyurethane resin, ionizing radiation curable resin, ultraviolet absorbing resin, etc. Among these, polyester resin or acrylic resin is preferred, and polyester resin is more preferred.

[0033] The number average molecular weight (Mn) of the resin material used in the protective layer is preferably from 5,000 to 30,000, more preferably from 8,000 to 25,000, from the viewpoint of robustness and durability.

[0034] The glass transition point (Tg) of the resin material used in the protective layer is preferably from 40° C. to 90° C., more preferably from 50° C. to 80° C., from the viewpoint of robustness and durability.

[0035] The content of the resin material in the protective layer is preferably from 70.0% by mass to 100.0% by mass, and more preferably from 80.0% by mass to 99.0% by mass, from the viewpoint of fastness and durability.

[0036] The protective layer preferably contains wax particles in order to impart slipperiness and improve abrasion resistance. The wax used in the release layer described above can be used as the wax, and among them, synthetic hydrocarbon wax is preferable, and it is more preferable to use wax that has been oxidized or acid-modified in terms of dispersibility in solvents and affinity with resin materials. The wax content in the protective layer is preferably 1.0% by mass or more and 10.0% by mass or less in terms of imparting slipperiness.

[0037] The protective layer may contain various additives within the range that does not impair the various functions required of the protective layer. Examples of the additives include inorganic / organic particles, surfactants, antioxidants, etc.

[0038] The thickness of the protective layer is preferably from 0.5 μm to 5.0 μm, more preferably from 1.0 μm to 3.0 μm, from the viewpoints of robustness, durability, and film tearability.

[0039] The protective layer can be formed by dispersing or dissolving the above-mentioned materials in an appropriate solvent to prepare a coating liquid, and coating the coating liquid on a release layer formed on a substrate by a known means such as roll coating, reverse roll coating, gravure coating, reverse gravure coating, bar coating, or rod coating to form a coating film, and then drying the solvent.

[0040] (Receiving layer) The intermediate transfer sheet of the present invention has an image receiving layer provided on a substrate, which is laminated in this order with a release layer and a protective layer. The image receiving layer is the outermost layer of the intermediate transfer sheet, and is a layer that receives the color material layer that is primarily transferred from a thermal transfer sheet having a color material layer, and has characters or images formed from the color material layer of the thermal transfer sheet on its surface. The image receiving layer also exhibits adhesiveness to the transferee during secondary transfer, and is a layer that adheres to the transferee.

[0041] The image receiving layer can suitably use a resin that develops adhesiveness when heated, such as an acrylic resin, an epoxy resin, a styrene resin, an ethylene-vinyl acetate copolymer resin, a vinyl chloride-vinyl acetate copolymer resin, a urethane resin, a polyester resin, an olefin resin, etc., and can contain one or more of these.

[0042] The image receiving layer may contain various additives within the range that does not impair the various functions required of the image receiving layer, such as a plasticizer, a defoamer, a surfactant, an antioxidant, a dispersant, and a tackifier.

[0043] The thickness of the image receiving layer is preferably 0.1 to 3.0 μm, more preferably 0.3 to 2.0 μm, from the viewpoints of image receiving performance during primary transfer, adhesion and film tearability during secondary transfer.

[0044] The image-receiving layer can be formed by dispersing or dissolving the above-mentioned materials in a suitable solvent to prepare a coating liquid, and coating the coating liquid on a release layer and a protective layer laminated on a substrate by a known means such as roll coating, reverse roll coating, gravure coating, reverse gravure coating, bar coating, or rod coating to form a coating film, and then drying the solvent.

[0045] (peel strength) In order to improve the transferability of the transfer layer of the intermediate transfer sheet to a recipient of various materials, it is better for the peel strength between the substrate and the release layer of the intermediate transfer sheet to be small, but if the peel strength is too small, problems such as the release layer peeling off from the substrate during manufacture or handling, or transfer failure during primary transfer to the transfer layer with a thermal transfer sheet may occur. In order to avoid these problems and improve the transferability of the transfer layer of the intermediate transfer sheet to a recipient of various materials, it is preferable that the peel strength of the transfer layer of the intermediate transfer sheet, measured by the following measurement method, is 0.03 N / 18 mm or more and 0.20 N / 18 mm or less.

[0046] (Peel force measurement method) The intermediate transfer sheet is cut to a width of 25 mm, and an 18 mm wide adhesive tape is attached to the image receiving layer surface of the intermediate transfer sheet so that it is parallel to the length direction and does not extend beyond the width direction of the intermediate transfer sheet. A 19.6 N (2 kgf) rubber roller is rolled back and forth twice over the adhesive tape to bond it, and the sheet is left to stand for 24 hours in an environment of 23±2°C and 50±10% RH. After that, a T-peel test is performed using a tensile testing machine at a peel speed of 3.0 m / min in an environment of 23±2°C and 50±10% RH, and the peel force at this point is measured.

[0047] <Thermal transfer sheet> The intermediate transfer sheet of the present invention can form letters or images on a receiving material by using a thermal transfer sheet having a colorant layer to perform a second transfer of letters or images that have been primarily transferred onto an image receiving layer onto the receiving material.

[0048] The thermal transfer sheet having a colorant layer used in the intermediate transfer sheet of the present invention (hereinafter referred to as thermal transfer sheet) is a thermal transfer sheet having at least one colorant layer provided on one side of a substrate, and preferably has a heat-resistant slipping layer on the other side of the substrate. The thermal transfer sheet may also have a release layer and / or peeling layer between the substrate and the colorant layer, or the colorant layer may be formed of multiple layers.

[0049] (base material) As the substrate for the thermal transfer sheet, various plastic films for the intermediate transfer sheet of the present invention can be used. The thickness of the substrate is usually about 2 to 12 μm, and in order to improve heat transfer, the thickness is preferably in the range of 2 to 6 μm.

[0050] (color material layer) When no release layer or the like is provided between the substrate and the colorant layer, the colorant layer is a layer that is directly laminated on the substrate. The colorant layer can be formed by adding a pigment or dye, which is a colorant, to a resin that serves as a binder. The colorant layer may contain particles for the purpose of improving the film cutability of the colorant layer during transfer, or may contain wax for the purpose of improving transferability. In addition, a pigment dispersant or other additives may be used as appropriate.

[0051] The resin material contained in the colorant layer may be, for example, an acrylic resin, a vinyl resin, a polyester resin, a urethane resin, a polyamide resin, an epoxy resin, or a rubber-based resin, but from the viewpoints of the film tearability of the colorant layer during primary transfer to the intermediate transfer sheet, adhesion to the image receiving layer, and adhesion to the transferee during secondary transfer, it is preferable to use a resin with excellent adhesion such as an acrylic resin or an epoxy resin. The content of the resin component contained in the colorant layer is preferably 50.0% by mass or more and 90.0% by mass or less of the solid content of the colorant layer from the viewpoints of adhesion to the transferee and ensuring a colorant content that provides sufficient print density.

[0052] The thickness of the color material layer is preferably 0.3 μm or more and 2.0 μm or less from the viewpoints of primary transferability, print density, and adhesiveness during secondary transfer.

[0053] The colorant layer can be formed by dispersing or dissolving the above-mentioned materials in a suitable solvent to prepare a coating liquid, coating the coating liquid on a substrate by a known method such as roll coating, reverse roll coating, gravure coating, reverse gravure coating, bar coating, or rod coating to form a coating film, and then drying the solvent.

[0054] The thermal transfer sheet is preferably provided with a heat-resistant slipping layer on the substrate surface opposite to the substrate surface on which the color material layer is provided. By providing the heat-resistant slipping layer, damage to the substrate of the thermal transfer sheet caused by the thermal head during primary transfer to the transfer layer of the intermediate transfer sheet in a thermal transfer printer can be reduced. If the substrate is damaged, the thermal head may stick to the substrate during printing, preventing the printer from running smoothly, which is known as sticking. By providing the heat-resistant slipping layer, such sticking can be prevented.

[0055] The material of the heat-resistant slipping layer can be any material that has been conventionally used in thermal transfer sheets without any particular restrictions. In consideration of heat resistance to thermal heads, low dynamic friction coefficient at high temperatures, and cost, silicone-modified urethane resins, silicone-modified acrylic resins, silicone resins, or mixtures thereof are particularly preferred as the material of the heat-resistant slipping layer.

[0056] The heat-resistant slipping layer may contain other additives such as particles, a lubricant, and an antistatic agent.

[0057] The thickness of the heat-resistant slipping layer is preferably 0.05 μm or more and 0.80 μm or less in order to achieve a good sticking prevention effect and to prevent a decrease in thermal conductivity.

[0058] The heat-resistant slipping layer can be formed by the same method as that for the color material layer.

[0059] (Transferred object) As the transferee to which the characters or images formed on the transfer layer of the intermediate transfer sheet of the present invention are transferred, various kinds of transferees can be used, but cards are particularly suitable as the transferee. Examples of materials for cards include polyvinyl chloride (PVC), polyethylene terephthalate (PET), polyethylene-co-1,4-cyclohexylene dimethylene terephthalate (PETG), etc.

[0060] Methods for transferring (secondary transfer) characters or images formed by thermal transfer (primary transfer) using a thermal transfer sheet from an intermediate transfer sheet to a transfer-receiving material by pressing and heating include a thermal transfer printer equipped with a thermal head, a heat roll, and a heat-pressure plate transfer method. Of these, in order to transfer the transfer layer of the intermediate transfer sheet to a transfer-receiving material such as various cards over the entire surface, transfer using a heat roll is preferred. EXAMPLES

[0061] The present invention will be described in more detail with reference to the following examples and comparative examples, although the present invention is not limited to these examples.

[0062] <Intermediate transfer sheet> [Preparation of release layer coating solution] The following materials for the release layer were mixed in the proportions shown in Table 1 to prepare release layer coating solutions 1 to 13 for use in the intermediate transfer sheets of the Examples and Comparative Examples. (Release layer material) Polyester urethane resin A (solvent solution, solids content 45%, Tg-30℃, Mn21,000) Polyester urethane resin B (solvent solution, solids content 30%, Tg-22℃, Mn32,000) Polyester resin C (solvent solution, solids content 35%, Tg-15℃, Mn28,000) Polyester resin D (solvent solution, solids content 30%, Tg-5℃, Mn25,000) Polyester Resin E (solvent solution, solids content 41%, Tg 4℃, Mn 23,000) Polyester resin F (solvent solution, solids content 30%, Tg 7℃, Mn 23,000) Polyester resin G (100% solids, Tg67℃, Mn17,000) Thermoplastic resin A (Acrylic resin, Tg105℃, Mn25,000) ·Thermoplastic resin B (Acrylic resin, Tg105℃, Mn280,000) ·Thermoplastic resin C (Ketone resin, Tg50℃, Mn650) Colloidal Silica (Organic solvent dispersed colloidal silica, solid content 30%, average particle size 12 nm) Oxidized polyethylene wax (Solvent dispersion, solid content 10%, average particle size 6μm, wax melting point 123℃)

[0063] [Table 1]

[0064] [Preparation of protective layer coating solution] The materials were mixed in the following ratio to prepare a protective layer coating liquid for use in the intermediate transfer sheet. (Formulation of protective layer coating liquid) Polyester resin (100% solids, Tg60℃, Mn8,000) 23.75 parts by mass Solvent dispersion of polyethylene oxide (Solid content 10%, average particle size 6μm, melting point 123℃) 12.50 parts by mass Toluene 3.00 parts by weight Methyl ethyl ketone 57.75 parts by weight Propylene glycol monomethyl ether acetate 3.00 parts by mass

[0065] [Preparation of image-receiving layer coating liquid] The materials were mixed in the following ratio to prepare an image receiving layer coating liquid to be used for the intermediate transfer sheet. (Formulation of image receiving layer coating liquid) Acrylic resin (Solid content 100%, Tg 105℃, Mn 25,000) 15.00 parts by mass Bisphenol A epoxy resin (100% solids, softening point 144℃, Mn3,800) 3.50 parts by mass Vinyl chloride-vinyl acetate copolymer (100% solids, Tg70℃, Mn50,000) 1.50 parts by mass Methyl ethyl ketone 77.60 parts by weight Propylene glycol monomethyl ether acetate 2.40 parts by weight

[0066] Example 1 [Preparation of intermediate transfer sheet] (Formation of peeling layer) A 16-micron-thick polyethylene terephthalate film was used as a substrate, and one side of the film was coated with release layer coating solution 1 by gravure coating so that the dried thickness would be 1.0 μm, and then heated and dried to form a release layer. (Formation of protective layer) A protective layer coating solution was applied onto the release layer formed above by gravure coating so that the thickness after drying would be 2.0 μm, and then dried by heating to form a protective layer. (Formation of Image Receiving Layer) Onto the protective layer thus formed, the image receiving layer coating liquid was applied by gravure coating so that the thickness after drying would be 0.5 μm, and the image receiving layer was formed by heating and drying, thereby producing an intermediate transfer sheet having a layer structure of substrate / peeling layer / protective layer / image receiving layer.

[0067] Example 2 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating liquid 1 in Example 1 was changed to the release layer coating liquid 2.

[0068] Example 3 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 3.

[0069] Example 4 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 4.

[0070] Example 5 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 5.

[0071] Example 6 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 6.

[0072] Comparative Example 1 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 7.

[0073] Comparative Example 2 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 8.

[0074] Comparative Example 3 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 9.

[0075] Comparative Example 4 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 10.

[0076] Comparative Example 5 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 11.

[0077] Comparative Example 6 An intermediate transfer sheet was produced in the same manner as in Example 1, except that the release layer coating liquid 1 in Example 1 was changed to the release layer coating liquid 12.

[0078] Comparative Example 7 An intermediate transfer sheet was prepared in the same manner as in Example 1, except that the release layer coating solution 1 in Example 1 was changed to the release layer coating solution 13.

[0079] <Thermal transfer sheet> [Preparation of premix for heat-resistant slip layer] The materials were mixed and dispersed in the following proportions to prepare a premix for the heat-resistant slip layer. (Premix for heat-resistant slip layer) Silicone urethane resin solution (25% solids) 32.33 parts by weight Melamine-formaldehyde resin particles (Average particle size: 0.2 μm, solid content 100%) 0.30 parts by mass Methyl ethyl ketone 67.37 parts by weight

[0080] [Preparation of heat-resistant slip layer coating fluid] Using the above-prepared premix for heat-resistant slipping layer, materials were mixed in the following ratio to prepare a coating liquid for heat-resistant slipping layer to be used in a thermal transfer sheet. (Formulation of coating fluid for heat-resistant slip layer) Premix for heat-resistant slip layer: 29.75 parts by weight Polyisocyanate solution (solid content 45%) 4.50 parts by weight Methyl ethyl ketone 55.75 parts by weight Toluol 10.00 parts by weight

[0081] [Preparation of color layer coating liquid] The materials were mixed and dispersed in the following proportions to prepare a colorant layer coating liquid for use in a thermal transfer sheet. (Formulation of colorant layer coating liquid) Acrylic resin (Molecular weight 30,000, Tg 75℃, solid content 100%) 5.23 parts by mass Bisphenol A epoxy resin (Molecular weight 1,650, softening point 97℃, solid content 100%) 1.74 parts by mass Polyester polymer dispersant (100% solids) 3.15 parts by weight Carbon black 21.47 parts by weight Methyl ethyl ketone 36.26 parts by mass Toluene 30.00 parts by weight Propylene glycol monomethyl ether acetate 2.15 parts by weight

[0082] [Preparation of thermal transfer sheet] (Formation of heat-resistant slip layer) A 4.5 micron thick polyethylene terephthalate film was used as the substrate, and the heat-resistant slipping layer coating liquid was applied to one side of the film by bar coating so that the dried thickness would be 0.2 μm, and then the film was dried by heating to form a heat-resistant slipping layer. (Formation of colorant layer) The colorant layer coating liquid was applied by bar coating to the surface of the polyethylene terephthalate film opposite the surface on which the heat-resistant slipping layer was formed, so that the thickness after drying would be 0.7 μm, and the coating was heated and dried to form a colorant layer, thereby producing a thermal transfer sheet with a layer structure of heat-resistant slipping layer / substrate / colorant layer.

[0083] <Peeling force of transfer layer of intermediate transfer sheet> The intermediate transfer sheets of Examples 1 to 6 and Comparative Examples 1 to 7 were cut to a width of 25 mm x length of 150 mm, and the adhesive surface of an 18 mm wide adhesive tape (3M Japan Ltd., Scotch (registered trademark) Mending Tape 810) was attached to the image receiving layer surface of each intermediate transfer sheet so that it was parallel to the length direction so as not to protrude from the width direction of the intermediate transfer sheet, and a rubber roller of 19.6 N (2 kgf) was pressed twice back and forth from above the adhesive tape, and the tape was left for 24 hours in an environment of 23 ± 2 ° C. and 50 ± 10% RH, and then a T-shaped peel test was performed at a peel speed of 3.0 m / min using a tensile tester (SHINTO SCIENTIFIC CO., LTD., HEIDON-14) in an environment of 23 ± 2 ° C. and 50 ± 5% RH, and the peel force at that time was measured. The measurement results of each Example and Comparative Example are shown in Table 2.

[0084] <Evaluation of adhesion of transfer layer> The intermediate transfer sheets of Examples 1 to 6 and Comparative Examples 1 to 7 were cut into 100 mm squares, and each intermediate transfer sheet was rubbed once by hand, and visually checked for the presence or absence of the transfer layer falling off, and each was evaluated according to the following evaluation criteria. The evaluation results of each Example and Comparative Example are shown in Table 2. (Evaluation Criteria) ◯: The transfer layer does not fall off from the substrate even when rubbed with hands. △: When rubbed with hands, a small amount of the transfer layer fell off from the substrate. ×: Most of the transfer layer falls off from the substrate when rubbed with hands.

[0085] <Evaluation of transferability of transfer layer> Using the thermal transfer sheet prepared above, a predetermined print pattern was transferred under the primary transfer conditions described below onto the image receiving layer surface of each of the intermediate transfer sheets of Examples 1 to 6 and Comparative Examples 1 to 7. Next, the transfer layer of each intermediate transfer sheet onto which the predetermined print pattern was transferred was transferred to a transfer receiving body under the secondary transfer conditions described below, and evaluated according to the following evaluation criteria. The evaluation results of each of the Examples and Comparative Examples are shown in Table 2. (Primary transfer conditions) Thermal transfer printer: SATO SG-408R Print speed: 4 inches / second Applied energy: Energy 3B (Secondary transfer conditions) Transfer method: Roll-type thermal transfer machine Roll temperature: 190℃ (surface temperature) Roll pressure: 118N Feed speed: 35mm / sec -Substrate: PVC card (dimensions: width 54mm x length 85.6mm x thickness 0.76mm) (Evaluation Criteria) ○: When the transfer target was visually inspected, the entire transfer layer was reliably transferred to the entire surface of the transfer target. Furthermore, no remaining untransferred transfer layer was observed after the transfer layer on the intermediate transfer sheet side was removed. Δ: When the transfer receiving material was visually inspected, it appeared that the entire transfer layer had been reliably transferred to the entire surface of the transfer receiving material, but after the transfer layer on the intermediate transfer sheet side had been removed, fine transfer layers were found to remain untransferred. ×: When the transfer receiving body was visually inspected, it was confirmed that there were some parts on the transfer receiving body where the transfer layer was not transferred.

[0086] <Evaluation of burrs on transfer layer> The edge of the transferee to which the secondary transfer was performed in the transferability evaluation was observed visually and using a 5x magnifying lens, and was evaluated according to the following evaluation criteria. The evaluation results for each of the examples and comparative examples are shown in Table 2. (Evaluation Criteria) ◯: No burrs were observed on the transfer layer at the edge of the transfer target. Δ: The transfer layer had burrs on the edge of the transfer target, and the amount of the transfer layer protruding from the edge was less than 0.5 mm. ×: There was a burr on the transfer layer at the edge of the transferred object, and the amount of the transfer layer protruding from the edge was 0.5 mm or more.

[0087] <Abrasion resistance evaluation> For the transfer material to which the secondary transfer was performed in the transferability evaluation, a load of 4.9 N / cm was applied to the printed pattern of the transferred transfer layer. 2 An abrasion resistance test (testing machine: crock meter) was conducted by running a cotton cloth back and forth 500 times on the same sheet, and the extent of damage to the printed pattern was visually confirmed and evaluated according to the following evaluation criteria. The evaluation results of each example and comparative example are shown in Table 2. However, Comparative Example 4 and Comparative Example 7 were not evaluated due to poor transferability. (Evaluation Criteria) ○: No damage was observed in the printed pattern. △: The print pattern was partially damaged. ×: The print pattern was significantly damaged.

[0088] <Alcohol resistance evaluation> For the transferee to which the secondary transfer was performed in the transferability evaluation, a part of the printed pattern of the transferred transfer layer was immersed in ethanol (Kanto Chemical's first-class ethanol, concentration 99.5%) for 20 minutes, and after drying, the state of the printed pattern was visually confirmed and evaluated according to the following evaluation criteria. The evaluation results of each example and comparative example are shown in Table 2. However, Comparative Example 4 and Comparative Example 7 were not evaluated due to poor transferability. (Evaluation Criteria) ◯: The same as the unimmersed portion, and there was no change in the transfer layer before and after immersion. Δ: Whitening was observed on the surface of the transfer layer compared to the unimmersed portion. ×: Dropping of the printed pattern was observed.

[0089] [Table 2] [Explanation of symbols]

[0090] 1: Intermediate transfer sheet 2: Base material 3: Release layer 4:Protective layer 5: Receiving layer 6: Transfer layer

Claims

1. The intermediate transfer sheet is characterized in that it comprises a substrate and, as a transfer layer, at least a release layer, a protective layer and an image receiving layer laminated thereon, in that order, the release layer contains a polyester resin and / or a polyester urethane resin having a glass transition point of -30°C or more and -5°C or less, colloidal silica, a thermoplastic resin and a wax, and the solid content of the release layer contains the polyester resin and / or the polyester urethane resin in an amount of 2.0% by mass or more and 8.0% by mass or less, and the colloidal silica in an amount of 60.0% by mass or more and 70.0% by mass or less.

2. 2. The intermediate transfer sheet according to claim 1, wherein the peel strength of the transfer layer of the intermediate transfer sheet, as measured by the following measurement method, is 0.03 N / 18 mm or more and 0.20 N / 18 mm or less. (Method of measuring peel strength) The intermediate transfer sheet is cut to a width of 25 mm, and an adhesive tape with a width of 18 mm is attached to the image-receiving layer surface of the intermediate transfer sheet so that it is parallel to the length direction and does not protrude beyond the width direction of the intermediate transfer sheet. A rubber roller of 19.6 N (2 kgf) is moved back and forth twice over the adhesive tape to bond it, and the tape is left to stand for 24 hours in an environment of 23±2°C and 50±10% RH. After that, a T-peel test is performed using a tensile tester at a peel speed of 3.0 m / min in an environment of 23±2°C and 50±5% RH, and the peel force at this time is measured.

Citation Information

Patent Citations

  • Intermediate transfer sheet

    JP2004351639A

  • Thermoelectric printer and production method of printed matter

    JP2019104207A